The Students’ Perception of Instagram Accounts in Improving English Speaking Skills - Rahma Utari; Nora Fitria; Muhammad Usman (English LAnguage Study and TEaching, 2023)
This study aimed to determine students' perceptions of English learning accounts on Instagram in improving speaking skills and to find out what effects students get from English learning accounts on Instagram in improving speaking skills. The research method used in this study was a mixed–method design. The population in this study were all English education students at Serambi Mecca University, while the selected sample of this study were odd-semester students of English Education who actively used Instagram and also followed English learning accounts on Instagram. They were consisting of 8 semester-1 students, 7 semester-3 students, 12 students from semester 5, and 7 students from semester 7. The sampling technique used was purposive sampling. This study used a questionnaire and an interview as instruments. Quantitative data were collected from the questionnaire using a Likert scale. While from the interview, qualitative data was gathered using a semi-structured set of questions. The data from the questionnaire were analyzed using the percentage formula, while the data from the interview was described in detailed words. This research found that 97% of students believe that the material shared by English learning accounts on Instagram was easy to understand, and 100% of students stated that they were motivated by material shared by English learning accounts on Instagram. It was concluded that accounts that share English learning materials on Instagram can be learning media for students.